Governing technology use by public authorities: What can and should be done? - Røhl, Ulrik (Politica, 2023)
Both in Denmark and abroad, discussions of the consequences of public authorities’ use of technology abound. Advantages and disadvantages of use of automated, administrative decision-making can be perceived as an embodiment of authorities’ use of technology in general. The article calls for increased management of use of automated, administrative decision-making to, among other consequences, prevent an increased imbalance between state apparatus and individual citizens. Hoping to stimulate further debate, three policy suggestions are put forward: i) strengthen relevant professional expertise particularly among high and mid-level public servants; ii) appoint an expert committee focusing on the need for supplementary legislation and guidance; and iii) increased focus and knowledge among regulatory authorities with a particular focus on technical and organizational aspects of automated, administrative decision-making.